PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING, INQUIRI DAN KONVENSIONAL TERHADAP PRESTASI BELAJAR SEJARAH DITINJAU DARI MINAT BELAJAR SISWA (STUDI EKSPERIMENTAL KELAS XI SMA NEGERI SE KABUPATEN BIMA TAHUN PELAJARAN 2015/2016) - Rosdiana, R.; Djono, D.; Musadad, Akhmad Arif (HISTORIKA, 2017)
This research aims to find out: (1) The difference of effect between Problem Based Learning, Inquiry, and Conventional model on learning achievement history, (2) The difference effect between students who have high interest and low interest of learning achievement history, (3) the interaction effect between the uses of learning model with interest in learning achievement history.This research is quantitative research with experimental method. The populations in this study are all students of SMA Negeri in Bima regency NTB in 2015/2016 Academic Year. Sampling was done by cluster random sampling technique. The research sample are 84 students, they are: 30 students of experiment class Problem Based Learning, 24 students of experimental class Inquiry in SMA Negeri 1 Madapangga and 30 Conventional control class in SMA Negeri 1 Bolo. The instrument uses to collect the data are questionnaires interest and learning achievement history test.The Hypothesis test is use two-way analysis of variance 3x2 with different cells. The results of the research show that: (1) There is differences between the effects of the use of learning model Problem Based Learning (PBL), Inquiry learning model, and conventional learning on the learning achievement history. This is evidenced by Fcount >Ftable(5.562 > 2.33) at the 5% significance level.(2) The difference effect between students who have high interest and low interest of learning achievement history.This is evidenced by Fcount > Ftable(103.243 > 2.33) at the 5% significance level.(3) There is no significant interaction between the learning model and interest in learning achievement of history. This is evidenced by Fcount> Ftable(1.577 < 2.33) at the 5% significance level.